The performance of 1% solution of baking soda as the mouthwashing for elderly xerostomia patients on the salivary secretion - Ariyanti, Ririn; Tjahajawati, Sri; Mariam, Marry Siti (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2018)
Introduction: The ageing process in older adults could cause a decreasing salivary secretion. Indicators of salivary secretion could be measured by observing an increasing salivary volume and pH, and a decreasing salivary viscosity. This study was aimed to observe the performance of 1% solution of baking soda on the salivary secretion of elderly xerostomia patients. Methods: The study used the quasi-experimental method with purposive sampling technique. The subjects were 24 older adults who were administered with 1% solution of baking soda. Results: The results showed that the averages volume, pH, and viscosity of the saliva before rinsing with 1% solution of baking soda were lower than after rinsing with the solution (p < 0.005). The average values of volume and pH of saliva before rinsing of 1% solution of baking soda were 0.15ml/min and 5.4, respectively, whilst after rinsing with the solution were 0.14ml/min and 7.42, respectively. The difference in saliva viscosity before and after rinsing with the solution showed that there were changes in the viscosity from frothy to watery. Conclusion: 1% solution of baking soda solution was able to increase the salivary secretion of elderly xerostomia patients, observed from an increasing salivary volume and pH, and a decreasing salivary viscosity after rinsing with 1% solution of baking soda.